The Impact of ODI on Job Resources in relation to Employee Engagement: A case study in a private Floor Tile Manufacturing company in Thailand - Phakdeesattayaphong, Pirata; Chungviwatanant, Ph.D., Sming (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
This research studies the impact of ODI on Job Resources (Supervisor Support, Job Autonomy, Performance Feedback, and Co-worker Support) in relation to Employee Engagement. For business to gain competitive advantage, the focus on new technology or good strategy must also include the human capital. The support and commitment of people is imperative in successful organizations. Thus, building an engaged workforce can be one of the strategic initiatives for a company to sustain organizational success. Using Action Research, this study was conducted at a local floor tile manufacturing factory. Six interventions were conducted with 27 participants over six months (May-Nov 2013). The ODI process design was based on Cummings & Worley’s Effective Change Management and Tayko’s Whole Brain Literacy. The researcher also set up a Control Group of 26 other participants who received no intervention. The results showed that (l) Age, Length of service in the h Company, and Job Position did not have effect on level of Employee Engagement; (2) Job Resources and Employee Engagement were significantly increased after ODI; and (3) Job Resources had a statistically significant relationship with Employee Engagement. Keywords: Employee Engagement, Work Engagement, Job Resources, Supervisor Support, Job Autonomy, Performance Feedback, Co-worker Support